LGBT Inclusive Athletic Departments as Agents of Social Change - George B. Cunningham (University of Kansas Libraries, 2015)
Despite advances, prejudice against lesbian, gay, bisexual, and transgender (LGBT) individuals continues to plague many areas of sport, including intercollegiate athletics. There are, however, some athletic departments that are inclusive of LGBT athletes, coaches, and administrators, and that have inclusive organizational cultures and practices. In this paper, the author draws from an institutional theory perspective to suggest these athletic departments act as agents of social change, working to deinstitutionalize norms of exclusivity and heterosexism, articulating a viable alternative, and then working to reinstitutionalize new structures, processes, and norms of LGBT diversity and inclusion.